2018
DOI: 10.3892/ol.2018.8434
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of RIP140 in triple‑negative breast cancer inhibits the growth and proliferation of cancer cells

Abstract: The aim of the present study was to investigate the expression of receptor interacting protein 140 (RIP140) in triple-negative breast cancer (TNBC), and its association with the prognosis of patients with TNBC. A total of 179 patients with breast cancer were included in this study, with 41 cases of TNBC and 138 cases of non-TNBC. Immunohistochemical staining and western blotting were used to detect the protein expression of RIP140 in the cancerous and paracancerous tissues, revealing that expression of RIP140 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…We, and other groups, have also reported that RIP140 plays crucial roles in tumorigenesis, promoting (Aziz et al, 2015;Rosell et al, 2014;Yu et al, 2018) or impairing breast tumor cell proliferation (Docquier et al, 2010;Jalaguier et al, 2017). In colorectal cancers, RIP140…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…We, and other groups, have also reported that RIP140 plays crucial roles in tumorigenesis, promoting (Aziz et al, 2015;Rosell et al, 2014;Yu et al, 2018) or impairing breast tumor cell proliferation (Docquier et al, 2010;Jalaguier et al, 2017). In colorectal cancers, RIP140…”
Section: Introductionmentioning
confidence: 78%
“…Moreover, RIP140 acts as a tumor suppressor, high expression of RIP140 correlating with good prognosis of colorectal cancer patients (Lapierre et al, 2014). In breast cancer, we, and other groups, have reported that RIP140 promotes (Aziz et al, 2015;Rosell et al, 2014;Yu et al, 2018) or impairs mammary tumor cell proliferation (Docquier et al, 2010;Jalaguier et al, 2017). Whether RIP140 is involved in the glucose metabolism of cancer cells and, if so, whether this directly affects tumor proliferation is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, GBP1 was described as a tumor suppressor in colon cancer [33]. These observations remind of RIP140 which has a protective role in colon [34] or triple negative breast cancer [13,35] whereas a high expression is associated with stomach cancer [36] as well as a shorter overall survival of cervical cancer patients [37]. GBP1 and RIP140 are a good illustration of tissue specificity of gene activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, RIP140 acts as a tumor suppressor, high expression of RIP140 correlating with good prognosis of colorectal cancer patients [24,25]. In breast cancer, we, and other groups, have reported that RIP140 promotes [26][27][28] or impairs mammary tumor cell proliferation [29,30]. Whether RIP140 is involved in the glucose metabolism of cancer cells and, if so, whether this directly affects tumor proliferation is still unknown.…”
Section: Introductionmentioning
confidence: 99%